Conceptualising and managing trade-offs in sustainability assessment - Morrison Saunders, Angus; Pope, Jennifer (Elsevier Inc., 2013)
One of the defining characteristics of sustainability assessment as a form of impact assessment is that it provides a forum for the explicit consideration of the trade-offs that are inherent in complex decision-making processes. Few sustainability assessments have achieved this goal though, and none has considered trade-offs in a holistic fashion throughout the process. Recent contributions such as the Gibson trade-off rules have significantly progressed thinking in this area by suggesting appropriate acceptability criteria for evaluating substantive trade-offs arising from proposed development, as well as process rules for how evaluations of acceptability should occur. However, there has been negligible uptake of these rules in practice. Overall, we argue that there is inadequate consideration of trade-offs, both process and substantive, throughout the sustainability assessment process, and insufficient considerations of how process decisions and compromises influence substantive outcomes.This paper presents a framework for understanding and managing both process and substantive trade-offs within each step of a typical sustainability assessment process. The framework draws together previously published literature and offers case studies that illustrate aspects of the practical application of the framework. The framing and design of sustainability assessment are vitally important, as process compromises or trade-offs can have substantive consequences in terms of sustainability outcomes delivered, with the choice of alternatives considered being a particularly significant determinant of substantive outcomes. The demarcation of acceptable from unacceptable impacts is a key aspect of managing trade-offs. Offsets can be considered as a form of trade-off within a category of sustainability that are utilised to enhance preferred alternatives once conditions of impact acceptability have been met. In this way they may enable net gains to be delivered; another imperative for progress to sustainability. Understanding the nature and implications of trade-offs within sustainability assessment is essential to improving practice.